IMPACT OF INDUSTRY-ORIENTED SKILL DEVELOPMENT PROGRAMS ON EMPLOYABILITY OF MANAGEMENT STUDENTS IN TAMIL NADU: THE MEDIATING ROLE OF EXPERIENTIAL LEARNING AND CAREER SELF-EFFICACY - Anandharaja, E.; Kavitha, S.; Radhakrishnan, M.; K C, Ranjithaa; S, Sudha; Poovaraghavan, J. (ShodhKosh: Journal of Visual and Performing Arts, 2026)
With the changing environment in the field of higher education, the employability of management graduates has become a top priority alongside the growing demands of the industry and the skill shortage. This paper examines the effects of industry-based skill development initiatives on employability of management students in Tamil Nadu with particular emphasis on the mediation roles of both experiential learning and career self-efficacy. The research design adopted was quantitative and a structured questionnaire was used to gather data among final year undergraduate and post graduate management students. The research utilizes Structural Equation Modeling (SEM) to address the correlation of the variables as well as testing the hypotheses. Industry-oriented skill development programs are shown to impact employability indirectly and directly in a highly positive way. Experiential learning is reported to be particularly important in improving the practical aspects of students and their problem solving skills, hence making them employable. Equally, the career self-efficacy plays a crucial role in determining the confidence of students in their ability to perform the job which enhances their employment preparedness. The findings also establish that there is chain mediation effect in that career self-efficacy is boosted by experiential learning, which culminates to better employability outcomes. It is believed that this research will add to the already existing literature by incorporating the pedagogical and psychological approaches into one cohesive system and also offer an empirical evidence based on the context of management education in Tamil Nadu. The results also provide valuable suggestions to schools, governments and industry players in planning successful skill acquisition programs and curriculum reviews. On the whole, the study highlights the importance of the holistic approach to education that is based on integrated practical exposure, experiential learning, and confidence-building to increase graduate employability.